Takayasu’s arteritis during pregnancy: A case report (Indian Journal of Case Reports, 2024)
Takayasu’s arteritis (TA) is also known as aorto arteritis having an incidence is 13/per million population. Here, we report the case of a 30-year-old woman gravida 2, para 1, who was admitted for safe delivery at 38 weeks of pregnancy. Clinical examination revealed an absence of radial pulse and blood pressure (BP) in both upper limbs and lower limbs BP recording showed 150/90 mm Hg with a pulse rate of 112/min. She was a known case of TA diagnosed during her first pregnancy. An elective cesarean section was done and a healthy male baby weighing 3.2 kg was delivered. The postnatal period was uneventful. She was discharged on the 8th day. A magnetic resonance imaging (MRI) angiogram was done before the second pregnancy. There was complete occlusion of the left common carotid artery from the origin with occlusion of the left internal carotid artery and there was collateral refilling of the left anterior cerebral artery and middle cerebral artery from the posterior communicating artery. The left vertebral artery showed circumferential wall thickening with hypointense flap within.